2016
DOI: 10.1089/jir.2015.0174
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Interferon Regulatory Factor-8 Expression in Myeloid–Tumor Interactions

Abstract: Perturbations in myelopoiesis are a common feature in solid tumor biology, reflecting the central premise that cancer is not only a localized affliction but also a systemic disease. Because the myeloid compartment is essential for the induction of adaptive immunity, these alterations in myeloid development contribute to the failure of the host to effectively manage tumor progression. These "dysfunctional" myeloid cells have been coined myeloid-derived suppressor cells (MDSCs). Interestingly, such cells not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…Importantly, as in mouse models, MDSC presence in human cancer carries significant prognostic value (8, 11). Intriguingly, PMN-MDSCs predominate in both tumor models and cancer patients (12, 13); yet, the mechanisms behind this bias have remained incompletely understood (12). Thus, despite advances in our understanding of the importance of MDSCs in neoplasia, there is much less known regarding the precise origin of MDSCs, why PMN-MDSCs dominate the response and what transcriptional events govern this decision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, as in mouse models, MDSC presence in human cancer carries significant prognostic value (8, 11). Intriguingly, PMN-MDSCs predominate in both tumor models and cancer patients (12, 13); yet, the mechanisms behind this bias have remained incompletely understood (12). Thus, despite advances in our understanding of the importance of MDSCs in neoplasia, there is much less known regarding the precise origin of MDSCs, why PMN-MDSCs dominate the response and what transcriptional events govern this decision.…”
Section: Introductionmentioning
confidence: 99%
“…The production of and subsequent differentiation of GMPs are events regulated by lineage-instructive transcription factors. One such transcription factor, interferon regulatory factor-8 (IRF8), is specifically expressed at this stage in myeloid development and is hypothesized to dictate GMP differentiation into either granulocytes (IRF8 lo ) or monocytes (IRF8 hi ) (13, 1618). This essential role for IRF8 was revealed using IRF8-deficient (IRF8 −/− ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the ARI-induced DC activated phenotype correlated well with the enhanced capability of these cells to specifically migrate toward ARI-treated colorectal cancer cells. One of the most important factors regulating DCcancer cell interactions is IRF8 (49), which acts through epigenetic regulation (50). We previously reported that IRF8 expression is progressively downmodulated during melanoma growth in mice and in human metastatic melanoma cells with respect to primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to understand MDSC accumulation in cancer, a number of studies have analyzed potential genetic and molecular factors. Several studies have reported interferon regulatory factor-8 (IRF-8), as well as the STAT family of transcription factors (STAT1, STAT3, STAT5, STAT6), as having potential roles in their development (11, 2024). IRF-8 has been shown to be downregulated, resulting in increased levels of MDSCs (2024).…”
Section: Mdsc Regulation In Neoplastic Diseasementioning
confidence: 99%